Social Conflict Among Religious Groups in the Perspective of Sociology of Religion - Komang Ariyanto (Jurnal Humaya: Jurnal Hukum, Humaniora, Masyarakat, dan Budaya, 2023)
Social conflicts between religious communities are a social and cultural issue that still needs to be addressed. They pose a challenging phenomenon within society, creating tension and fractures between individuals and groups with different beliefs. These tensions often pose a threat to the harmony and cohesion among religious communities in Indonesia. Therefore, this study aims to examine the phenomenon of social conflicts among religious communities from the perspective of sociology of religion. Employing a qualitative method with a literature study approach, it explores social conflicts among religious communities from the viewpoint of sociology of religion. The research findings indicated that interfaith dialogue is recognized as an evolving effort to foster associational and social interactions among religious believers. The significant role of the sociology of religion lies in its integral part in the continuous social process, shaping tolerance among religious followers.